The Roles of Neuropeptide Y (Npy) and Peptide YY (Pyy) in Teleost Food Intake: A Mini Review - Daniel Assan (Life, 2021)
Neuropeptide Y family (NPY) is a potent orexigenic peptide and pancreatic polypeptide family comprising neuropeptide Y (Npy), peptide YYa (Pyya), and peptide YYb (Pyyb), which was previously known as peptide Y (PY), and tetrapod pancreatic polypeptide (PP), but has not been exhaustively documented in fish. Nonetheless, Npy and Pyy to date have been the key focus of countless research studies categorizing their copious characteristics in the body, which, among other things, include the mechanism of feeding behavior, cortical neural activity, heart activity, and the regulation of emotions in teleost. In this review, we focused on the role of neuropeptide Y gene (Npy) and peptide YY gene (Pyy) in teleost food intake. Feeding is essential in fish to ensure growth and perpetuation, being indispensable in the aquaculture settings where growth is prioritized. Therefore, a better understanding of the roles of these genes in food intake in teleost could help determine their feeding regime, regulation, growth, and development, which will possibly be fundamental in fish culture.